Pengaruh Opini Audit, Tindak Lanjut Hasil Audit, dan Desentralisasi Fiskal terhadap Tingkat Korupsi Pemerintah Provinsi di Indonesia - Finna Khairatun Hisanun Muhardi; Halkadri Fitra (Universitas Negeri Padang, 2026)
This study aims to examine the influence of audit opinions, audit follow-up, and fiscal decentralization on the level of corruption in provincial governments in Indonesia from 2020 to 2023. This is a quantitative study using a causal associative method. The population in this study is all provinces in Indonesia from 2020 to 2023. The sampling technique in this study used purposive sampling. The total sample size is 132 samples. The data used in this study are secondary data obtained from the official websites of the Corruption Eradication Commission, the Financial Audit Agency, and the Central Bureau of Statistics. The analysis was conducted using multiple regression analysis. Based on the results of the analysis, it was found that audit opinions have a significant negative effect on the level of corruption. Meanwhile, follow-up on audit results have a significant positive effect on the level of corruption, and fiscal decentralization does not have a significant effect on the level of corruption.